International Perspectives on Assistive Technologies for Autism and Intellectual Disabilities: Findings from a Delphi Study - Paulina Tsvetkova; Carla Sousa; Daniel Beiderbeck; Aneta M. Kochanowicz; Branislav Gerazov; May Agius; Tomasz Przybyła; Merita Hoxha; Alan H. Tkaczyk (Disabilities)
Advancements in Assistive Technologies (ATs) have significantly improved the quality of life and autonomy for people with intellectual disabilities and autistic individuals, enhancing education, social interaction, employment, and mental health. Nevertheless, several barriers still emerge in the daily implementation of such technologies, highlighting the need to explore them in depth. Using a two-round Delphi method, we conducted a research study with an expert panel of 284 participants from 31 European countries, collecting quantitative and qualitative data. We tested ten future-oriented projections and gathered insights on participants’ backgrounds and attitudes towards ATs for this demographic. To enhance representation, experts from academia, service providers, industry, and disability organizations, as well as individuals with disabilities and their families, were included. Although the findings show strong consensus among experts on the positive impact and desirability of ATs for promoting the social inclusion of people with intellectual disabilities and autistic individuals, they also reveal differing perceptions across expert groups and identify two distinct future scenarios linked to different cultural, social, and economic hindrances. In this sense, our study provides diverse global perspectives, with the potential to help governing bodies understand the expectations, concerns, and needs related to ATs for often underrepresented groups–people with intellectual disabilities and autistic individuals in this case.